The Influence of Learning Facilities and Class Management on Learning Effectiveness - Nurbaiti, Tiara; Lian, Bukman; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aimed to analyze the effect of learning facilities and classroom management on learning effectiveness at SD Negeri in Sematang Borang District, Palembang. The type of research method used is the quantitative research method with data collection techniques through questionnaires, observation, and documentation. The population was 119 teachers of SD Negeri in Sematang District, Palembang and the sample size was 54 teachers. The instrument test was carried out outside the sample of 30 teachers who were taken randomly from the population of SD Negeri in Sematang District, Palembang. Data were analyzed using simple linear regression and multiple linear regression techniques. Based on the results of the data analysis showed that in the test of the influence of learning facilities variables on the learning effectiveness variable through the t-test obtained acount value of 5.254 greater than the t-table 2.007, it was concluded that there was an influence of learning facilities on the learning effectiveness of SD Negeri in Sematang Borang District, Palembang, as well as the test of the influence of classroom management variables on the learning effectiveness variable obtained a t-count value of 5.005 greater than the t-table value 2.007, it was concluded that there was an influence of classroom management on the learning effectiveness of SD Negeri in Sematang Borang District, Palembang. The test continues by looking at the effect of learning facilities variables and classroom management variables together on the learning effectiveness variable obtained tcount value 18.605 greater F-table 3.168 at a significant level of 5% so it is concluded that there is an effect of learning facilities and classroom management together on the effectiveness of learning in SD Negeri in Sematang Borang District, Palembang.